A utilização de técnicas de mediação pela advocacia como instrumentos de prevenção de conflitos no âmbito da holding familiar e a efetivação do direito fundamental de acesso à justiça - Silva, Luísa Gasparini e (2024)
It seeks to verify whether the use of mediation, from a technical perspective, by lawyers, in the process of establishing the family holding, can contribute to the prevention of conflicts between the subjects involved. In methodological terms, the research is guided by Karl Raymund Popper's hypothetical-deductive method, which supports the carrying out of falsification tests that basically consisted of a critical assessment of the degree of pertinence and applicability of the objectives pursued by mediation techniques in the context of the family holding. As a hypothesis, we consider that the introduction of mediation techniques by lawyers in the constitution of the family holding company can contribute to the prevention of family and succession conflicts. We maintain that by providing an environment conducive to constructive dialogue, the use of these techniques emerges as a fundamental tool in facilitating communication and reciprocal understanding of the interests of each family member, establishing solid foundations for lasting and successful family relationships within the scope of holding. The research was structured into four chapters. Based on the assumption that conflicts are inevitable and can bring constructive results when properly managed, chapter I addresses the elements of conflict theory and its implications for human interactions. The epicenter of this analysis lies in family conflicts, notably in intricate succession issues, at which point the effectiveness of the judicial process in this specific context is questioned. Chapter II discusses the fundamental right of access to justice, analyzed from a substantial perspective and under the parameters of coexistence justice. In this trajectory, the research highlights the Universal Access to Justice Movement, as well as the obstacles identified and the proposed mitigation measures, with an emphasis on the third wave of the movement, which deals with the dissemination of alternative methods to the judicial process. Chapter III is dedicated to the study of mediation, as well as the analysis of its conceptual and philosophical foundations, as well as the understanding of its three perspectives: as a process, as a philosophy and as a technique, the latter being the core of the present research. Chapter IV concludes the dissertation, when the application of mediation techniques by lawyers in the context of family holdings is analyzed with the aim of verifying the materialization of the primary objectives of this method. At the end of this journey, it was concluded that the use of mediation from a technical perspective, in the act of establishing the family holding, contributes to the prevention of conflicts between the individuals involved, as long as the objectives sought by the mediation techniques are fully achieved, These are: in-depth exploration of the interests at stake, strengthening dialogue, reestablishing the intersubjective relationship, transforming the parties, empowering those involved and building an agreed solution